The Iron Witch - Mahoney, Karen (Australia Random House Ltd, 2011)
Freak. That's what her classmates call seventeen-year-old Donna Underwood. When she was seven, a horrific fey attack killed her father and drove her mother mad. Donna's own nearly fatal injuries from the assault were fixed by magic -- the iron tattoos branding her hands and arms. The child of alchemists, Donna feels cursed by the magical heritage that destroyed her parents and any chance she had for a normal life. The only thing that keeps her sane and grounded is her relationship with her best friend, Navin Sharma. When the darkest outcasts of Faerie -- the vicious wood elves -- abduct Navin, Donna finally has to accept her role in the centuries old war between the humans and the fey. Assisted by Xan, a gorgeous half-fey dropout with secrets of his own, Donna races to save her friend -- even if it means betraying everything her parents and the alchemist community fought to the death to protect. -book cover.
Keywords: Magic -- Alchemists -- Interpersonal relations